Perancangan Sistem Informasi Penyewaan Lapangan Futsal Berbasis Web (Studi Kasus Awk Futsal Center Bekasi Timur) - Rina Fitriani -; Untung Yudo Asmoro; Satria .; Rino Cahyadie (Jurnal ICT: Information Communication & Technology, 2023)
Sport is a necessity especially in big cities like Bekasi, the availability of a futsal field at the East Bekasi AWK Futsal Center as a means of fulfilling this. The problem is that there are more and more tenants, so admins who serve transactions also have more difficulties in service, are ineffective and are still conventional. The purpose of this study is to design a web-based futsal field rental information system using the Waterfall method in order to develop software with a short cycle so as to speed up the software development process. The design of a web-based futsal field rental information system can also make it easier for customers and admins to carry out futsal field rental transactions and recap reports both daily and monthly.